Microencapsulation of a hydrophilic model molecule through vibration nozzle and emulsion phase inversion technologies. (9th April 2013) - Dorati, Rossella; Genta, Ida; Modena, Tiziana; Conti, Bice
Abstract : Introduction : The goal of the present work was to evaluate and discuss vibration nozzle microencapsulation (VNM) technology combined to lyophilization, for the microencapsulation of a hydrophilic model molecule into a hydrophilic polymer. Materials and methods : Fluorescein-loaded alginate microparticles prepared by VNM and emulsion phase inversion microencapsulation (EPIM) were lyophilized. Morphology, particle size distribution, lyophilized microspheres stability upon rehydration, drug loading and in vitro release were evaluated. Results and discussion : Well-formed microspheres were obtained by the VNM technique, with higher yields of production (93.3–100%) and smaller particle size (d50 138.10–158.00) than the EPIM microspheres. Rehydration upon lyophilization occurred in 30 min maintaining microsphere physical integrity. Fluorescein release was always faster from the microspheres obtained by VNM (364 h) than from those obtained by EPIM (504 h). Conclusion : The results suggest that VNM is a simple, easy to be scaled-up process suitable for the microencapsulation hydrophilic drugs.